Silicato de cálcio e magnésio,dinamizado pelo método homeopático, nas culturas do milho e do arroz - Pereira, Suele Augusto (Universidade Federal de São Carlos, 2022)
Corn and rice are among the world's top foods and producing them sustainably is essential. In this sense, the use of homeopathic preparations can help in the development of these cereals, with an impact on the absorption of nutrients and on the soil. The aim of this work was to study the effects of steel slag (calcium and magnesium silicate) on different homeopathic dynamizations, on the initial development of corn and rice and on the chemical characteristics of the soil. The following treatments were studied: calcium magnesium silicate (SiCaMg), in the following dynamizations: 8DH,13DH, 21DH, 34DH, 4CH and 17CH; a control, without application of SiCaMg and homeopathic preparations (SPH) and a treatment with SiCaMg in weight dose. Biometric data, water use efficiency, soil chemical characteristics and water infiltration rate after maize and rice cultivation were evaluated. Calcium magnesium silicate (CaMgSi), both in weight and in homeopathic preparations, showed lower values for corn in relation to plant height (CaMgSi and 21DH), leaf area index, fresh and dry mass of the plants. leaves (34DH and 21DH), stem fresh and dry mass (CaMgSi, 21DH, 17CH, 34DH and 8DH), water use efficiency (CaMgSi, 21DH, 17CH, 34DH and 8DH). In relation to rice, biometric data and data from and EUA showed no differences between treatments. In corn, foliar calcium (Ca) and magnesium (Mg) contents were higher for the control, and CaMgSi for corn had a similar effect to 8DH, 4CH, 21DH, 34DH, 17CH, decreasing its absorption. In rice, similarly, it happened for Mg levels, but not for Ca. Regarding the chemical characteristics of the soil, there was an increase in pH, with a decrease in potential acidity and differences in the vii contents of phosphorus (P), potassium (K) and sulfur (S) and micronutrients. There was a decrease in the infiltration rate after application of treatments 34DH, 17CH, 8DH and 4CH in relation to the control. (CaMgSi, 21DH, 4CH and 8DH). In this way, it was verified that it is possible to select homeopathic dynamizations that correspond to the effects of the application of calcium and magnesium silicate in weight dose, with potential use of the technology rural producers.
Calcium and magnésium silicte, dynamized by the homeopatic method, applied in cor ande rice crops
Keywords: Escória de siderurgia; Homeopatia; Orysa sativa; Silício; Zea Mays; Steel slag; Homeopathy; Silicon; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO